1991
DOI: 10.1002/jez.1402580113
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human sperm acrosome reaction by effectors of the adenylate cyclase/cyclic AMP second‐messenger pathway

Abstract: The acrosome reaction of spermatozoa appears to be analogous to various somatic cell exocytotic events which involve cascade reactions, i.e., transmission of an external signal across the cell membrane resulting in activation of an "amplifier" enzyme and the generation of a second messenger. Using a synchronous acrosome reaction system (De Jonge et al., J. Androl., 10:232-239, '89a), it was found that analogues of the second-messenger cAMP, dibutyryl cAMP (dbcAMP) and 8-bromo cAMP, stimulated the acrosome reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 44 publications
5
62
1
3
Order By: Relevance
“…Cyclic AMP, in turn, is believed to stimulate the cAMP-dependent kinase (24), which itself induces sperm tail protein phosphorylation (25) with subsequent increase in sperm motility (26). Improving acrosomal reaction is another benefi cial effect of pentoxifylline drug, demonstrated that this induction is not due to a Ca 2+ -infl ux in the sperm cell but is according to increasing the intracellular level of cAMP as the second messenger of acrosomal reaction (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic AMP, in turn, is believed to stimulate the cAMP-dependent kinase (24), which itself induces sperm tail protein phosphorylation (25) with subsequent increase in sperm motility (26). Improving acrosomal reaction is another benefi cial effect of pentoxifylline drug, demonstrated that this induction is not due to a Ca 2+ -infl ux in the sperm cell but is according to increasing the intracellular level of cAMP as the second messenger of acrosomal reaction (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms and the signal transduction pathways mediating the processes of acrosome reaction are partially defined: changes in protein phosphorylation and dephosphorylation of sperm proteins, including Ca 2C -dependent processes, seem to play a primary role in the second messenger regulatory mechanisms (for a review, see Benoff 1998, Breitbart & Naor 1999, Baldi et al 2000, Guraya 2000, Topfer-Petersen et al 2000, Urner & Sakkas 2003. There is evidence for the involvement of cAMP-dependent protein kinase (PKA) in the mammalian acrosome reaction: adenylate cyclase activity and cAMP generation increased during this process in human spermatozoa (De Jonge et al 1991); adenylate cyclase stimulators such as forskolin, and the cAMP analogue dibutyryl cAMP, induced the acrosome reaction in a dose-dependent manner in human and ram spermatozoa (Anderson et al 1992, Garde & Roldan 2000, Harrison & Meizel 2000; and PKA inhibitors have been reported to suppress human sperm acrosome reaction (Harrison & Meizel 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PF inhibits cyclic adenosine monophosphate (cAMP) phosphodiesterase, thus increasing intracellular cAMP concentration (5,7) and tyrosine-phosphorylation at the tail level (8). cAMP has a role in sperm kinematics and in the acrosome reaction second-messenger system (7,9). Treatments that increase intracellular cAMP concentrations often cause an increase in sperm motility and kinematics as well as in the agonist-induced acrosome reaction (9) and fertilization rates (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…cAMP has a role in sperm kinematics and in the acrosome reaction second-messenger system (7,9). Treatments that increase intracellular cAMP concentrations often cause an increase in sperm motility and kinematics as well as in the agonist-induced acrosome reaction (9) and fertilization rates (5,6). Also, it has been postulated that PF has the ability to scavenge reactive oxygen radicals (10,11).…”
Section: Introductionmentioning
confidence: 99%